Agrostis tsomgoensis (Poaceae, Agrostidinae)––a new pooid grass species from Sikkim Himalaya, India - Prasad, Dileshwar; Tiwari, Smita; Sharma, Sangam; Yadav, Rekha; Agnihotri, Priyanka (Phytotaxa, 2025)
A new species, Agrostis tsomgoensis, sp. nov., is described and illustrated from Sikkim, India. It is distinguished from other known species of Agrostis in having glumes almost twice the lemma length, lemma unawned and glabrous, palea half of the lemma length, and anthers 0.33–0.66 mm long. Comparison with similar species, A. clavata, A. scabra and A. micrantha, is presented. A detailed morphological description, photograph, distribution map, and taxonomic notes for this species are also provided.